算法歧视的敏捷治理: -以 D短视频平台为例. - 高 进; 刘 聪 (Journal of Xi'an Jiaotong University (Social Sciences), 2024)
As an emerging technological force based on big data and machine deep learning, algorithms have a profound impact on the development process of economy and society with their powerful data analysis and processing, independent learning and decision-making capabilities, and human beings are entering the era of algorithms where everything can be “calculated”. However, the abuse and generalization of algorithms based on the logic of “algorithm is king” also exposes the dark side of algorithms, spawning serious algorithmic discrimination, which has become a major social risk that disrupts market order, damages fairness and justice, and infringes on citizens' rights. Therefore, it is urgent for the government to clarify the internal mechanism of algorithm discrimination, explore the appropriate algorithm governance path, and respond to the realistic questions like “how does algorithm discrimination arise? “ and “what are the solutions to this problem?”. However, most of the existing researches on algorithmic discrimination focus on regulation, supervision and other aspects to explore how to achieve algorithmic governance, which shows that the governance subject is single and governance measures lag behind with low governance quality efficiency, resulting in the "whack-a-mole" governance cycle with poor effect. As a governance concept proposed for the supervision of emerging industries such as big data and artificial intelligence, agile governance can effectively adapt to the intractable problems of algorithmic discrimination and meet the actual needs of algorithmic governance by relying on its advantages in many aspects such as governance subjects, governance tools, governance values and governance paradigms. Therefore, the government uses the agile governance concept to empower algorithm to govern algorithm discrimination and improve the quality and efficiency of algorithm governance. This study carried out "field work" based on the content of D short video platform through participatory investigation, analyzed the logical mechanism of algorithm operation of short video platform, summarized the forms and causes of algorithm discrimination, and explored feasible measures and practical approaches to algorithm governance. It is found that the setting of user circles, issue scenes and induction boundaries constitutes the algorithm "black box" of the short video platform, and generates the invisible operation logic of the digital marketing of accurate portraits, the reproduction of the relationship between fields, and the re-capture of users with interests first. The dual role of subjective and objective conditions is the root cause of algorithm discrimination, and user portrait, personalized recommendation, and using big-data analysis to price tour products to the disadvantage of existing customers constitute the main forms of algorithm discrimination. It is an effective means to overcome the trap of algorithm discrimination to form a logical closed loop of agile governance on the basis of pre-monitoring and early warning, control resolution in the process, and summary and improvement afterwards. In addition, this paper found that measures like increasing the research and development of algorithm technology to enhance the ability of scientific and technological innovation, to achieve the combination of self-discipline and other-discipline, to create a dynamic governance pattern with the participation of multiple subjects, and other diversified measures can further help crack algorithm discrimination and achieve good algorithm governance. Based on the research results of scholars, this study tries to aggregate the two research propositions between algorithmic discrimination and agile governance, and builds an analytical framework of agile governance, which has certain research value for enriching the theoretical basis and practical approach of algorithmic discrimination in agile governance, constructing responsible and reliable algorithms, improving the rationality of algorithms, and realizing algorithmic agile governance. In addition, the government can adopt agile governance in discrimination governance, so as to shape the Chinese solution of algorithmic governance in terms of overall intellectual governance, collaborative governance and co-governance, dynamic governance, and optimization algorithms.